2017
DOI: 10.1051/shsconf/20173300075
|View full text |Cite
|
Sign up to set email alerts
|

Factor of Awareness in Searching and Sharing of Halal Food Product among Muslim Families in Malaysia

Abstract: Abstract. Information search activities are fundamental in information sharing, especially for the context of information confusion in the market for halal products. This research paper will focus on awareness factor in information searching and sharing of halal products in the Muslim families. Recently, the halal issue has become the hot topic as it involves community religious tenets. This study aims to enrich communications literature in terms of information seeking in halal food products. The sample of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 2 publications
2
15
0
7
Order By: Relevance
“…These two relationships positively influence the respondents' perception of wholesomeness of halal food represented by the variations of respondents in determining the importance of a halal assurance system to search for halal food information. This finding is in line with [11] who found that Muslim families have high levels of awareness towards halal food products…”
Section: Discussion and Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These two relationships positively influence the respondents' perception of wholesomeness of halal food represented by the variations of respondents in determining the importance of a halal assurance system to search for halal food information. This finding is in line with [11] who found that Muslim families have high levels of awareness towards halal food products…”
Section: Discussion and Resultssupporting
confidence: 91%
“…Previous studies have recently reported several related factors influencing information seeking behaviors for halal food productions concerning ingredients, awareness of an individual, habit, Islamic laws, and attitude. For example, [11] studied the ambiguity in determining the halal product due to the obstacles of the existing scenarios in the industry among 340 Muslims in Bangi, Selangor, Malaysia. The study instigated that awareness factor is significantly correlated with information seeking behavior among Muslim families.…”
Section: Related Studiesmentioning
confidence: 99%
“…A food can be categorized as halal when the preparation, processing, storage, packaging, handling and transportation meet the Islamic law (Yusoff and Adzharuddin, 2017). Generally, there are several guidelines regarding halal food set by Islamic law: 1) All raw materials and ingredients used must be halal, 2) All the allowed animal should be slaughtered based on Islamic rites.…”
Section: Concept Of Halal Foodmentioning
confidence: 99%
“…Yusoff dan Adzharuddin (2017) menyebutkan bahwa konsumen muslim yang memiliki kesadaran tinggi tentang kehalalan suatu produk akan secara aktif mencari informasi mengenai kehalalan produk tersebut dan kemudian akan membagikan informasi tersebut kepada orang-orang terdekat, seperti anggota keluarga. Kesadaran yang tinggi terhadap kehalalan produk menandakan bahwa konsumen tersebut memiliki komitmen religiositas yang tinggi (Ambali & Bakar, 2014;Yusoff & Adzharuddin, 2017). Berdasarkan argumen tersebut, hipotesis penelitian 3 ditetapkan sebagai berikut: H3 : Religiositas Islami berpengaruh terhadap eWOM…”
Section: Pengaruh Religiositas Islami Terhadap Kepuasan Destinasiunclassified